Development of 17 kV 4H-SiC PiN diode - 黄润华 陶永洪 汪玲 陈刚 柏松 栗锐 李赟 赵志飞 (Journal of semiconductors, 2016)
The design, fabrication, and electrical characteristics of a 4H-SiC PiN diode with breakdown voltage higher than 17 kV are presented. The three-zone JTE has been used in the fabrication. Numerical simulations have been performed to optimize the parameters of the edge termination technique. The epilayer properties of the N-type are 175/zm with a doping of 2 x 1014 cm-3. With the three-zone JTE, a typical breakdown voltage of 17 kV has been achieved.